Best practice in primary care pathology: review 2. Issue 2 (27th January 2006) - Smellie, W S; Forth, J O; McNulty, C A M; Hirschowitz, L; Lilic, D; Gosling, R; Bareford, D; Logan, E; Kerr, K G; Spickett, G P; Hoffman, J; Galloway, A; et al.
Abstract : This second best practice review examines five series of common primary care questions in laboratory medicine: (1) laboratory testing for allergy, (2) diagnosis and monitoring of menopause, (3) the use of urine cytology, (4) the usefulness of the erythrocyte sedimentation rate, and (5) the investigation of possible urinary tract infection. The review is presented in a question–answer format. The recommendations represent a précis of guidance found using a standardised literature search of national and international guidance notes, consensus statements, health policy documents, and evidence based medicine reviews, supplemented by MEDLINE EMBASE searches to identify relevant primary research documents. They are standards but form a guide to be set in the clinical context. Most are consensus rather than evidence based. They will be updated periodically to take account of new information.